The Application of Learning Community Strategy to Improve Speaking Skill - Effran Aderiza (Universitas Sulawesi Barat, 2018)
The Application of Learning Community Strategy to Improve Speaking Skill for Fourth Semester of English Department at Universitas Muhammadiyah Parepare,Supervised by Bahrun Amin and Ammang Latifa. This research is aimed at finding out: Whether The Application of Learning Community Strategy to Improve Speaking Skill for Fourth Semester of English Education at Universitas Muhammadiyah Parepare. This research used quasi experimental method. The populations were the fourth Semester in English Department in academic year of 2014-2015, consisted of 175 students with fours classes. The samples that were drawn by using random sampling technique consisted of 40 students, which are Class A as experimental group and Class B as Control group.The data were acquired by using speaking test. The speaking test will be applied in the pretest and posttest.The result of this research concluded that there was a significant difference the students who were taught speaking Learning Community Strategy. It is proved by statistic analysis of t-test (5.83) was higher than the t-table (1.734)